High Performance SWCNT Pressure Sensor (Journal of University of Babylon for Engineering Sciences, 2023)
In the current model, designed and simulated Carbon nanotubes (CNTs) on a circular diaphragm-based piezoresistive pressure sensor was studied. Single-walled Carbon nanotubes (SWCNTs) were used to check better sensitivity. The impact of altering the pressure on the displacement, current density, and von Mises stress was studied using a single CNTs and an array of CNTs. It was observed that increasing the pressure resulted in an increase in displacement, current density, and von Mises stress. The attained sensitivity of SWCNTs was 1.428*10^-11µA\Pa. Moreover, the effect of changing diameter on the resistance of CNT and the energy bandgap was studied. The design of the current study picked the diameter limits from 1nm to 4nm. It was found that raising the diameter led to reducing the energy bandgap from 0.426 eV to 0.10 eV and decreased the resistance from 2143kΩto 543kΩ at zero strain.